Features of the socio-economic security of Russia in the development of the system of compulsory medical insurance - E. V. Sinitsyna (Путеводитель предпринимателя, 2020)
The article «the health of the nation» is considered as one of the socio-economic aspects that shape the «quality of life» of the population, and the development of the compulsory health insurance system as the most important factor affecting the level of Russia’s socio-economic security.